The Invisible Show: Keys to Micro-Tales Through the Texts by Ana María Shua (Castilla. Estudios de Literatura, 2013)
This essay analyzes the characteristics of micro-tale literary genre through the works by Ana María Shua. In her fiction, the author presents a constant reflection about the genre, and shows the creating process from genre selection step to the final result; disclosing its basic characteristics. Thus, Ana María's short narrative becomes a poetic treatise of micro-tale built up by means of metafictional acts.